Waste shells of cockle (Clinocardium nuttalli) as solid catalysts for transesterification of calophyllum inophyllum L. oil to biodiesel production - Husni Husin; . Zuhra; Fikri Hasfita; Wahyu Rinaldi (Syiah Kuala University, 2013)
In this work, cockle (Clinocardium nuttalli) shell waste is massively produced by many restorant in Banda Aceh Indonesia. The cockle (Clinocardium nuttalli) shell is known high calcium; therefore it is potential to be used as calcium source of catalyst for transesterification reaction. The aim of thisresearch is to study the synthesis and characterization of Clinocardium nuttalli shell. Clinocardium nuttalli shell was prepared by calcinating the shell at 500 and 800°C. Synthesis of solid catalys was employed for transesterification reaction of calophyllum inophyllum L. oil. The reaction was carried out in batch reactor at temperature of 65oC and ratio of mrthanol:oil of 3:1 - 12:1. The synthesized samples were characterized by X-ray diffraction (XRD). Analysis data by XRD confirmed that the obtained crystal calcined at 500 oC areCaCO3 calcite, CaCO3 veterite, and CaO. XRD patterns of the colcined shell at 800 oC shows sharp peaks of crystalline phase of CaO. The best characteristics is obtained at calcined catalyst of 800oC with molar ratios of methanol:oil of 12:1, i.e. density 0.832 g/cm3, viscosity 4.92 cst, and yield 84.1%.